TREATMENT APPROACH OF TATTOO-HEAVY METAL'S DYE INDUCING ACUTE ULCERATIVE SKIN LESION - Muhi N. Salman; Saud. Albagdadi; Hale. Alobaidi (Scholar Express Journals, 2021)
The occurrence of tattoos –heavy metal's dye with associated adverse skin reaction markedly increased in the last two decades. A29 years –old female was suffering from persistent ulcerative crater lesion on her upper left hand in middle area of orange to red decorative tattoos near the shoulder joint due to underwent to magnetic resonance imaging (MRI) after car accident. Complete healing of ulcerative lesion was achieved by application treatment protocol combined of antibiotic, cortisone and topical AQUACEL Ag foam/ surgical (convaTec) wound dressing. Conclusion; Tattoos heavy metal-dye may induce skin reaction starting from simple inflammatory reaction to end up with breakdown of persistent skin reaction. Alongside regulation, standardization is an important element for implementation of high-quality requirements for tattoo inks and tattooing.
Keywords: Tatoos; AQUACEL; wound dressin; Magnetic resonance image